Viabilidade do uso de solo tropical e resíduo de construção civil em sistemas de cobertura de aterro sanitário - Dias, Mônica Carolina Ciríaco (2014)
The generation of construction waste (RCC) stands out for the quantity produced and the volume occupied in the array. Thus, is requiried to reuse this material and a viable alternative is the use in geotechnical works. The use of waste in geotechnical works, also allows replacement of the natural geotechnical materials, so that helps to reduce the uncontrolled exploitation of the deposits. In Brazil since the 1980s, there is research developed using construction waste in paving, where the use of these materials is promising and technologically appropriate. However, the use of massive paving does not guarantee recycling of this waste, because the market is not able to consume more than 50% of the material, resulting in the need for application in other types of geotechnical. Thus, this research aims to verify the technical feasibility of using RCC in landfill cover system. In terms of methodology, the physical characterization were performed (granulometry, Atterberg limits, density, chip and method of the methylene blue), hydro-mechanical tests (density, direct shear, permeability, filter paper) and erodibility (disaggregation test, crumb test, pinhole test and inderbitzen) in Soil samples, RCC and misture. The results showed that the soil and misture were characterized as low plasticity silt and RCC as silty sand. With permeability values, it was found that the soil and the mixture comply with the proposed permeability requirements for the top layer of coverage, but do not meet for the hydraulic barrier, mainly due to grain size arrangement having these materials. And the permeability of RCC isn´t appropriate to be used in any of these layers. The influence of deformation coefficients are larger than the pre-consolidation stress, since the deformation of the RCC is greater than the soil and mixing behavior are close to the RCC. As for the friction angle and cohesion obtained the RCC had values similar to those of granular soils and he sample of soil and the mixture obtained typical values of low plasticity clay. In analyzing the disaggregation of the three materials, and found that soil mixture is stable material in the presence of water unlike the RCC, which proved to be an unstable material in the presence of water. In relation to the test Inderbitzen, the RCC has greater mass loss of the sample soil as expected by that be a non-cohesive material. Moreover mixture showed the lowest weight loss value during the test. In the analysis of internal erosion Solo and the mixture are classified as a non-disintegrating and non-dispersive material and RCC is an easily disintegrating material, but not dispersive. With the analysis made it was found that the increase of percentage of 50% of tropical soil in RCC did the material had a better hydro-mechanical behavior compared to pure RCC as well as being a less erodible material. From the results, it is concluded that the mixture is a viable alternative for use in surface layer and protection in a landfill cover system.